Predictors of outcomes in outpatients with anorexia nervosa - Results from the ANTOP study - Wild, Beate; Friederich, Hans-Christoph; Schellberg, Dieter; Herzog, Wolfgang (Psychiatry research, 2016)
This study aimed to determine predictors of BMI and recovery for outpatients with anorexia nervosa (AN). Patients were participants of the ANTOP (Anorexia Nervosa Treatment of Out-Patients) trial and randomized to focal psychodynamic therapy (FPT), enhanced cognitive behavior therapy (CBT-E), or optimized treatment as usual (TAU-O). N=169 patients participated in the one-year follow-up (T4). Outcomes were the BMI and global outcome (recovery/partial syndrome/full syndrome) at T4. We examined the following baseline variables as possible predictors: age, BMI, duration of illness, subtype of AN, various axis I diagnoses, quality of life, self-esteem, and psychological characteristics relevant to AN. Linear and logistic regression analyses were conducted to identify the predictors of the BMI and global outcome.The strongest positive predictor for BMI and recovery at T4 was a higher baseline BMI of the patients. Negative predictors for BMI and recovery were a duration of illness >6 years and a lifetime depression diagnosis at baseline. Additionally, higher bodily pain was significantly associated with a lower BMI and self-esteem was a positive predictor for recovery at T4. A higher baseline BMI and shorter illness duration led to a better outcome. Further research is necessary to investigate whether or not AN patients with lifetime depression, higher bodily pain, and lower self-esteem may benefit from specific treatment approaches.
Gesehen am 12.08.2020